Effectiveness of individualised nutritional care plans to reduce malnutrition during hospitalisation and up to 3 months post-discharge: a systematic scoping review - Kari Ingstad; Lisbeth Uhrenfeldt; Ingjerd Gåre Kymre; Conni Skrubbeltrang; Preben Pedersen (BMJ Open)
Objectives The prevalence of malnutrition after hospitalisation is reported to be 20%–45%, which may lead to adverse outcomes, as malnutrition increases the risk of complications, morbidity, mortality and loss of function. Improving the quality of nutritional treatment in hospitals and post-discharge is necessary, as hospital stays tend to be short. We aimed to identify and map studies that assess the effectiveness of individualised nutritional care plans to reduce malnutrition during hospitalisation and for the first 3 months post-discharge.Design This was a systematic scoping review.Methods We systematically searched for all types of studies in the following databases: EMBASE, MEDLINE via PubMed, and the Cumulative Index to Nursing and Allied Health Literature, with no restriction on data or publication language. We also reviewed the reference lists of the included studies. The abstracts and full articles were simultaneously screened by two independent reviewers. Differences of opinion were discussed among the two investigators, and a third reviewer assisted with the discussion until consensus was reached. Studies in which the patients received an individual nutritional care plan related to their hospital stay and were followed up post-discharge were included. We then conducted a thematic content analysis of the extracted literature.Results Nine randomised controlled trial studies met the inclusion criteria: six were conducted in Scandinavian countries. All studies were mainly conducted among elderly patients (mean ages varied from 75 to 88 years). The review studies measured 10 different outcomes; the most common outcomes were nutritional status and readmission. Six studies reported one or more significant positive intervention effect. Inconsistent results were identified for four outcome variables.Conclusions Individualised nutritional care plans and follow-up home visits might improve patients’ nutritional status. However, there is need for a systematic review that assesses study quality and extends the time to 6 months post-discharge.